The Effect of Protected Lemuru Fish Oil Supplementation on In Vivo Nutrient Digestibility and Sheep Blood Profile - Ratri Ratna Dewi; Kustantinah Kustantinah; Muhlisin Muhlisin (Buletin Peternakan, 2022)
This research was intended to observe the effect of protected lemuru fish (Sardinella longiceps) oil for ruminants, especially for sheep. This study aimed to evaluate the digested nutrients and blood profile of sheep. This study was conducted in September-October 2020 in Dumbira Farm, Kalasan, Yogyakarta, using 12 sheep divided into 3 treatments with 4 replications each. Treatment P0 was Total Mixed Ration (TMR) without protected Lemuru fish oil (control), treatment P1 was TMR with 5% protected Lemuru fish oil, and treatment P2 was TMR with 10% protected Lemuru fish oil. The data were statistically analyzed using one way analysis of variance and continued with Duncan new Multiple Range Test for significant results. The results of this study indicated that the addition of 10% protected Lemuru fish oil in TMR feed had a significant effect (P<0,05) on the increased value of in vivo digestion of crude fiber and crude fat, but did not affect the digestibility of dry matter, organic matter, and protein. The addition of protected Lemuru fish oil did not cause hematological disorders showed by the blood profiles were in the normal range. In conclusion, protected lemuru fish oil supplementation had a favorable influence on the production performance without affecting blood profile of sheep.